JOURNEY OF PURSUING 1% LOSS PRODUCTION OPPORTUNITY IN FIELD X - Silaban, Meita
Loss Production is inevitable process of oil and gas operation including field X. Field X is a mature field that operates for over 50 years and currently operates with about 4% production loss due to well down. Most of well down or off due 2 major reasons: proactive job or intentional programs to improve well performance such as pump replacement, workover or stimulation and reactive job or unintentional well down due to pump failure, power outage, pipe leak, etc.